Perturbation of RNA homeostasis impairs mitochondrial respiration during poxvirus infection through excess RNA accumulation - Djamal Brahim Belhaouari; Anil Pant; Santiago Navarro-Forero; Fernando Cantu; Zhilong Yang (Proceedings of the National Academy of Sciences, 2026)
Induction of RNA degradation in infected cells is a strategy used by many viruses to promote efficient replication. Vaccinia virus, the prototype poxvirus and the vaccine platform for smallpox and mpox, encodes two decapping enzymes to accelerate mRNA and double-stranded RNA (dsRNA) degradation during infection, through functional coordination with host cell RNA exonuclease. Previous studies have largely focused on RNA degradation as a mechanism for regulating viral gene expression and evading innate immune sensing. Here, we show that impaired RNA degradation in vaccinia virus–infected cells, due to either depletion of viral decapping enzymes or cellular exonuclease, severely compromises mitochondrial respiration and integrity. We further demonstrated that accumulation of excess dsRNA and mRNA, including pseudouridine-modified RNAs, is sufficient to induce profound defects in mitochondrial respiration and integrity. Notably, this impairment occurs independently of interferon induction and dsRNA innate immune sensor Protein Kinase R. Moreover, excess RNA suppresses respiration in purified cell-free mitochondria and physically associates with mitochondria in cell-free and cellular contexts, supporting an immune-independent mechanism. Excess mRNA and dsRNA reduce mitochondrial membrane potential in both cells and purified mitochondria, indicating disruption of the proton gradient as the mechanism underlying impaired mitochondrial respiration and integrity. Together, these findings identify excess mRNA and dsRNA as perturbants of mitochondrial homeostasis in cells with dysfunctional RNA degradation during vaccinia virus infection, revealing a paradigm-shift concept linking RNA metabolism to mitochondrial function. The finding carries broad implications for understanding RNA and mitochondrial biology and RNA-based therapeutics and vaccines.